Challenges in cognitive psychotherapy of chronic depression - Jerotić, Stefan (Engrami, 2023)
Chronic depression poses a distinct psychotherapeutic challenge compared to acute depression, demanding a specialized approach, particularly within the framework of cognitive-behavioral therapy. Successful therapeutic intervention must consider various specificities of this condition, including: (1) challenges in establishing a therapeutic alliance, (2) avoidance as the dominant mechanism of maintenance, and (3) core beliefs regarding depression itself. The establishment of a therapeutic alliance is often complicated by the long-standing demoralization of the patient, requiring the therapist’s unique sensitivity and patience. Cognitive model of chronic depression designates avoidance as a pivotal maintenance mechanism of the disorder. Avoidance can be conceptualized in behavioral, cognitive, and emotional dimensions. Behavioral avoidance manifests as an inclination to evade or abstain from confronting situations or environmental stimuli that induce discomfort. Cognitive avoidance encompasses strategies for evading distressing thoughts or memories and can manifest through denial, excessive generalization, minimization, and rumination. Emotional avoidance comprises the suppression of unpleasant emotional states, often leading to pervasive emotional numbness. These avoidance mechanisms are interwoven with the individual’s beliefs about their depression. The perception of depression as a sign of personal weakness or a purely "biological" problem precludes linking the situational context to symptoms, thus intensifying the sense of helplessness. A comprehensive approach to psychotherapy of chronic depression necessitates the recognition and addressing of these challenges.